Tools of generative artificial intelligence in teaching English for specific purposes - Anna V. Malaeva; Tatiana P. Volkova; Tatiana A. Globa (Развитие образования)
The article is devoted to the possibilities of using generative artificial intelligence (GAI) tools in teaching English for specific purposes (ESP). The article examines innovative approaches to learning, being necessary due to the rapid development of technology and requirements of the modern labor market. It analyzes the prospects of GAI in ESP context, including a comparative description of the most popular AI tools. The authors explore the functionality, advantages, and limitations of these tools, their impact on teaching a professionally oriented foreign language. Examples of the successful application of GAI in university courses are given. The emphasis is made on the development of communication skills and the adaptation of educational materials to specific professional fields. The article discusses the results of the empirical study showing positive changes in students' learning motivation and progress. The use of GAI contributes to more effective and personalized learning, improves vocabulary, grammatical accuracy and writing skills. However, the successful implementation of GAI requires additional knowledge and training of teachers, as well as focusing on the educational context. Special attention is paid to the need for a balanced approach when using GAI in order to avoid dependence on technology and preserve the positive experience gained in the process of applying traditional teaching methods.